PEMANFAATAN LIMBAH KAYU SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN IPAS KELAS IV MIS LKMD WAEPERANG KABUPATEN BURU - Rifa Madura, Achmad; Syahid, Akhmad; Martini; Syahrul, Muhammad; Aidil Sudarmono R, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of utilizing wood waste as an interactive learning medium and to identify its benefits in the IPAS subject for fourth-grade students at MIS LKMD Waeperang. The research stems from students’ low understanding of IPAS material due to limited learning media. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The results of the study show that the utilization of wood waste as an interactive learning medium was carried out by processing available materials into a visual model representing the water cycle in IPAS learning. The presence of this media enabled students to grasp the concept more easily through direct observation of the processes displayed in a concrete form. Its use also encouraged active engagement, increased interest, and strengthened students’ understanding and participation throughout the learning process. In addition to helping teachers deliver the material more clearly and attractively, the use of wood waste also fostered environmental awareness by promoting the reuse of discarded materials as meaningful educational tools.